Effective Use of Automating Productivity to Improve e-Marketing Strategies for Entrepreneurial Projects - Shatti , Dhurgham Mohammed (American Journal of Economics and Business Management, 2025)
This study aims to identify the role played by the effective use of production automation in improving e-marketing strategies for entrepreneurial projects. The study also focused on the essential elements of effective use, through which productivity can be improved, to develop e-marketing strategies that can contribute to entrepreneurial leadership. The importance of this study stems from its emphasis on the role of the effective use of production automation in e-marketing strategies, which is a significant challenge facing companies in the current economy. 165 electronic questionnaires were distributed to customers who purchased the aforementioned company’s products. The statistical analysis program Smart PLS SPSS was used to analyze the research sample. The study results also showed that the effective use of production automation plays a significant role in achieving e-marketing strategies, as it can contribute to improving the performance of entrepreneurial projects and promoting innovation and change within companies. The study also revealed that customers who purchase products exhibit different preferences, reinforcing the importance of providing a distinctive customer experience. The most important recommendations are to enhance awareness and training, as companies are advised to develop strategies for the effective use of production automation to achieve e-marketing strategies and how to market and sell them effectively, and to qualify them to deal with customers seeking these products.